2012
DOI: 10.1080/01431161.2012.748992
|View full text |Cite
|
Sign up to set email alerts
|

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data

Abstract: P. Gong et al. land-cover classification system as well as the International Geosphere-Biosphere Programme (IGBP) system. Using the four classification algorithms, we obtained the initial set of global land-cover maps. The SVM produced the highest overall classification accuracy (OCA) of 64.9% assessed with our test samples, with RF (59.8%), J4.8 (57.9%), and MLC (53.9%) ranked from the second to the fourth. We also estimated the OCAs using a subset of our test samples (8629) each of which represented a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
807
3
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,372 publications
(907 citation statements)
references
References 92 publications
5
807
3
9
Order By: Relevance
“…The survey is composed of over 13,000 sampling blocks of 10× 10 km within Landsat images. Other large RSS used wall-to-wall sets of Landsat images with comparable results to the ones obtained by the FRA RSS (Gong et al 2013;Hansen et al 2013) or also MODIS images (Hansen et al 2010). The use of different forest definitions produces varying estimates of the forest area.…”
Section: The Forest Resources Assessmentmentioning
confidence: 59%
“…The survey is composed of over 13,000 sampling blocks of 10× 10 km within Landsat images. Other large RSS used wall-to-wall sets of Landsat images with comparable results to the ones obtained by the FRA RSS (Gong et al 2013;Hansen et al 2013) or also MODIS images (Hansen et al 2010). The use of different forest definitions produces varying estimates of the forest area.…”
Section: The Forest Resources Assessmentmentioning
confidence: 59%
“…It appears that separating 4 years old rubber stands remains problematic and therefore warrants a future investigation. While this research indicated that RF was favorable in terms of individual class accuracy, it should be noted that disagreement to select a better classifier between RF and SVM exists in the literature [Gong et al, 2013;Adam et al, 2014;Lawrence and Moran, 2015]. This may be sourced from various causes, including site- Figure 5.…”
Section: The Role Of Texturementioning
confidence: 99%
“…For artificial surfaces, it was also compared to other global land cover products for eight test areas around the world and accuracies ranged from 79% to 97%, outperforming both CLC and the FROM-GLC product of Gong et al [4]. There have been a few other studies that have independently compared GL30 to authoritative products in Italy [30], Germany [31] and water bodies in Scandinavian countries [32] and more recently, land cover in Iran [33], with high agreements, i.e., greater than 78%.…”
Section: Globeland30mentioning
confidence: 99%